40 years of the human T-cell leukemia virus: past, present, and future [version 1; referees: 2 approved] - Yutaka Tagaya; Masao Matsuoka; Robert Gallo (F1000Research, 2019)
It has been nearly 40 years since human T-cell leukemia virus-1 (HTLV-1), the first oncogenic retrovirus in humans and the first demonstrable cause of cancer by an infectious agent, was discovered. Studies indicate that HTLV-1 is arguably one of the most carcinogenic agents to humans. In addition, HTLV-1 causes a diverse array of diseases, including myelopathy and immunodeficiency, which cause morbidity and mortality to many people in the world, including the indigenous population in Australia, a fact that was emphasized only recently. HTLV-1 can be transmitted by infected lymphocytes, from mother to child via breast feeding, by sex, by blood transfusion, and by organ transplant. Therefore, the prevention of HTLV-1 infection is possible but such action has been taken in only a limited part of the world. However, until now it has not been listed by the World Health Organization as a sexually transmitted organism nor, oddly, recognized as an oncogenic virus by the recent list of the National Cancer Institute/National Institutes of Health. Such underestimation of HTLV-1 by health agencies has led to a remarkable lack of funding supporting research and development of treatments and vaccines, causing HTLV-1 to remain a global threat. Nonetheless, there are emerging novel therapeutic and prevention strategies which will help people who have diseases caused by HTLV-1. In this review, we present a brief historic overview of the key events in HTLV-1 research, including its pivotal role in generating ideas of a retrovirus cause of AIDS and in several essential technologies applicable to the discovery of HIV and the unraveling of its genes and their function. This is followed by the status of HTLV-1 research and the preventive and therapeutic developments of today. We also discuss pending issues and remaining challenges to enable the eradication of HTLV-1 in the future.